1974
DOI: 10.1029/rg012i003p00363
|View full text |Cite
|
Sign up to set email alerts
|

Observations of interactions between interplanetary and geomagnetic fields

Abstract: Magnetospheric effects associated with variations of the north‐south component of the interplanetary magnetic field (IMF) are examined in light of recent experimental and theoretical results. Although the occurrence of magnetospheric substorms is statistically related to periods of southward IMF, the details of the interaction are not understood. In particular, attempts to separate effects resulting directly from the interaction between interplanetary and geomagnetic fields from those associated with substorms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

1976
1976
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(33 citation statements)
references
References 108 publications
2
31
0
Order By: Relevance
“…1 and 2). This suggestion is corroborated by studies that have shown a strong positive correlation between the southward IMF component (B z ) and a variety of geomagnetic and auroral activity indices (Arnoldy, 1971;Foster et al, 1971;Rostoker et al, 1972;Burch, 1974;Garrett et al, 1974;Murayama and Hakamada, 1975). Figure 3b shows the plot of the H component on 10 and 11 June 1993 (solid line) (period No 1) compared with those of the reference quiet day levels (dashed line), over the African sector (UT=LT).…”
Section: Variations Of the Solar Wind Parameters And The Magnetic Indsupporting
confidence: 62%
“…1 and 2). This suggestion is corroborated by studies that have shown a strong positive correlation between the southward IMF component (B z ) and a variety of geomagnetic and auroral activity indices (Arnoldy, 1971;Foster et al, 1971;Rostoker et al, 1972;Burch, 1974;Garrett et al, 1974;Murayama and Hakamada, 1975). Figure 3b shows the plot of the H component on 10 and 11 June 1993 (solid line) (period No 1) compared with those of the reference quiet day levels (dashed line), over the African sector (UT=LT).…”
Section: Variations Of the Solar Wind Parameters And The Magnetic Indsupporting
confidence: 62%
“…These studies have established the importance of such interplanetary parameters as the north-south magnetic field component (B0, the solar wind speed (V), the interplanetary magnetic field (IMF), magnitude (B), and various combinations of these parameters (see reviews by Burch, 1974;Akasofu, 1977;and Russell, 1979). These studies have established the importance of such interplanetary parameters as the north-south magnetic field component (B0, the solar wind speed (V), the interplanetary magnetic field (IMF), magnitude (B), and various combinations of these parameters (see reviews by Burch, 1974;Akasofu, 1977;and Russell, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…Evans and Stone [1972] place this latitude between 75 ø and 80 ø near local noon and 75 ø and 76 ø near local midnight. From these high latitudes the geomagnetic field lines have been 'blown' far to the nightside of the earth, downwind, to form the outer regions of the magnetospheric tail where merging of the interplanetary and geomagnetic fields is most likely to occur [Burch, 1974]. We have demonstrated that the polar sector effects are strongest well above the 74 ø invariant latitude and thius within the open field line region.…”
mentioning
confidence: 99%